Estimating core-mantle boundary temperature from seismic shear velocity and attenuation - Deschamps, Frédéric; Cobden, Laura (Frontiers in Earth Science, 2022)
The temperature at Earth’s core-mantle boundary (CMB) is a key parameter to understand the dynamics and thermal evolution of our planet. However, it remains poorly known, with current estimate ranging from about 3000 K to more than 4000 K. Here, we introduce a new approach based on joint measurements of shear-wave velocity, VS, and quality factor, QS, in the lowermost mantle. Lateral changes in both VS and QS above the CMB provide constraints on lateral temperature anomalies with respect of a reference temperature, Tref, defined as the average temperature in the layer immediately above the CMB. The request that, at a given location, temperature anomalies inferred independently from VS and QS should be equal gives a constraint on Tref. Correcting Tref for radial adiabatic and super-adiabatic increases in temperature gives an estimate of the CMB temperature, TCMB. This approach further relies on the fact that VS-anomalies are affected by the distribution of post-perovskite (pPv) phase. As a result, the inferred Tref is linked to the temperature TpPv at which the transition from bridgmanite to pPv occurs close to the CMB. A preliminary application to VS and QS measured beneath Central America and the Northern Pacific suggest that for TpPv = 3500 K, TCMB lies in the range 3470-3880 K with a 95 % likelihood. Additional measurements in various regions, together with a better knowledge of TpPv, are however needed to determine a precise value of TCMB with our method.